Debt Financing Under Asymmetric Information. - Goswami, Gautam; Noe, Thomas H; Rebello, Michael J (Journal of Finance, 1995)
The authors analyze the optimal design of debt maturity, coupon payments, and dividend payout restrictions under asymmetric information. They show that, if the asymmetry of information is concentrated around long-term cash flows, firms finance with coupon-bearing long-term debt that partially restricts dividend payments. If the asymmetry of information is concentrated around near-term cash flows and there exists considerable refinancing risk, firms finance with coupon-bearing long-term debt that does not restrict dividend payments. Finally, if the asymmetry of information is uniformly distributed across dates, firms finance with short-term debt.